Government Agency Resources for Florida Blueberry Growers - Douglas A. Phillips; Jeffrey G. Williamson (EDIS)
Several federal, state, and local government offices and agencies offer assistance and resources to Florida blueberry growers. These include the University of Florida and IFAS Extension, the U.S. Department of Agriculture (USDA), the Florida Department of Agriculture and Consumer Services (FDACS), and various Florida water management districts. This publication summarizes some of the resources and assistance available from each of these agencies, along with website links as a starting point for growers to use in learning more about and accessing that assistance.